2016
DOI: 10.1155/2016/8749417
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Albumin Uptake and Processing Promote Albuminuria in OVE26 Diabetic Mice

Abstract: The importance of proximal tubules dysfunction to diabetic albuminuria is uncertain. OVE26 mice have the most severe albuminuria of all diabetic mouse models but it is not known if impaired tubule uptake and processing are contributing factors. In the current study fluorescent albumin was used to follow the fate of albumin in OVE26 and normal mice. Compared to normal urine, OVE26 urine contained at least 23 times more intact fluorescent albumin but only 3-fold more 70 kD fluorescent dextran. This indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Urinary microalbumin (UMA), a traditional marker representing damages of glomerular filtration barrier and glomerular hyperfiltration, increased gradually in a dosedependent manner since blood glucose reached 11.1 mmol/L. In recent years, UMA is believed to be primarily controlled by renal tubular epithelial cells, which represents tubular reabsorption dysfunction defined as "diabetic tubulopathy" (22)(23)(24). A good correlation was found between urinary albumin excretion and markers of tubular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary microalbumin (UMA), a traditional marker representing damages of glomerular filtration barrier and glomerular hyperfiltration, increased gradually in a dosedependent manner since blood glucose reached 11.1 mmol/L. In recent years, UMA is believed to be primarily controlled by renal tubular epithelial cells, which represents tubular reabsorption dysfunction defined as "diabetic tubulopathy" (22)(23)(24). A good correlation was found between urinary albumin excretion and markers of tubular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Increased Ps’alb was measured in glomeruli isolated from diabetic rats, even in those with mild proteinuria, suggesting that the assay is sensitive to early changes in renal function Albuminuria can be impacted by tubular reuptake of albumin resulting in variable urinary albumin-to-creatinine ratio values in experimental diabetic models. 35 When tubular reuptake of albumin was inhibited using an inducible transgenic megalin knockout mouse line, this resulted in a 10-fold increase in urinary albumin secretion in diabetic mice. 36 Because our Ps’alb assay measures albumin permeability directly, it circumvents this potential confounding factor and confirms that glomeruli are a target in diabetic kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Mori et al found that reabsorption of endogenous albumin was doubled in STZ-induced or Akita-inherited type 1 diabetic mice and reabsorption efficiency was reduced at the same time [ 30 ]. Protein accumulation may occur because of an increase in reabsorption or an insufficient ability to process and dispose of internalized protein by proximal tubule cells [ 31 ]. Further studies are warranted to determine whether albumin accumulation in diabetic rat tubules is due to enhanced albumin uptake or a failure to clear internalized albumin.…”
Section: Discussionmentioning
confidence: 99%